2015
DOI: 10.1136/postgradmedj-2014-133130
|View full text |Cite
|
Sign up to set email alerts
|

Workplace training for senior trainees: a systematic review and narrative synthesis of current approaches to promote patient safety

Abstract: Clinical supervision is the primary avenue for learning in postgraduate medical education but the most overlooked in the context of patient safety learning. The widespread implementation of short courses is not matched by evidence of rigorous evaluation. Supporting supervisors to identify teaching moments during supervision and to give weight to non-technical skills and technical skills equally is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…ten Cate building his definition of EPAs a few years after proposing them), this review learned lessons from examining the overall body of literature on EPAs in GME, new and old. Also, although publication date may have played a role, other reviews in medical education have identified similar variability in quality . This variability may indicate a need to broadly examine methods in medical education research or to develop methodological quality assessment tools better suited to the field of research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ten Cate building his definition of EPAs a few years after proposing them), this review learned lessons from examining the overall body of literature on EPAs in GME, new and old. Also, although publication date may have played a role, other reviews in medical education have identified similar variability in quality . This variability may indicate a need to broadly examine methods in medical education research or to develop methodological quality assessment tools better suited to the field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Scores on the QATSDD can range from 0 to 42 (qualitative and quantitative studies) or 48 (mixed‐methods studies). This assessment tool has been shown to produce good agreement and has been used in a number of different reviews pertaining to health services and medical education research . The QATSDD was applied to studies within both categories by two researchers independently and any disagreements were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, the Accreditation Council for Graduate Medical Education (ACGME) published the following 6 core patient safety competencies: patient care, medical knowledge, interpersonal and communication skills, professionalism, practise‐based learning and improvement, and systems‐based practice . These competencies are reflected in clinician training and as part of professional registration internationally …”
Section: Discussionmentioning
confidence: 99%
“…В таких обстоятельствах риск нежелательных, хотя порой высоковероятных по определению явлений, неблагоприятных исходов лечения и конфликтных ситуаций не просто возможен, но и неизбежен [2,10,11], а проблема предотвратимого вреда при оказании медицинской помощи -одна из шести проблем глобального здравоохранения [12]. Безусловным трендом современной хирургии следует признать постулат, что безопасность пациентов является основой для обеспечения качественной медицинской помощи [1,5].…”
Section: обзорыunclassified